Bibliotecas públicas e construção da cidadania: desafios no âmbito da Sociedade da Informação em Moçambique - Momade Amisse Ali (2011)
Examines the role and challenges of provincial public libraries in the building and development of citizenship in Mozambique. Provincial public library are intended as institution with great potential for providing adequate conditions of access and use of information and new ICT, and thus able to contribute to the strengthening of citizenship and participation in the information society in Mozambique. Moreover, far from devoting a mere adoption of new ICTs, building the information society in Mozambique is thought from the perspective of integration and optimization of the sociocultural and political aspects of information to economic and technological predominate in their prescription in Mozambique. In terms of methodology, was adopted a qualitative approach, which involved a literature search and a case study exploratory and descriptive. The Nampula provincial public library was chosen as a case study. Empirical research data were collected through unstructured observation of the environment of library, and an in-depth interview with the director of that. Equally were performed simple interviews with leaders of some institutions domiciled in Nampula province, to identify institutional relationships with our empirical object of research. Data was preliminarily collected between January and February 2010, and was being further developed through correspondence by e-mail to questions of clarification. The results of bibliographic and documentary search pointed to the prevalence of technological and economic criteria in the process of implementation of the information society in Mozambique. The results of the case study revealed that the Nampula provincial public library privileges in a large extent, the activities of (i) supporting the processes of teaching-learning and research, (ii) promoting books and reading habits, and (iii) dissemination of journalistic information. Thus, the main challenges to this library within the Information Society in Mozambique refer to extending the scope of its users (involving potential users), and boosting their other duties, mainly contribute to the dissemination of public domain information and organize lectures and discussions on topics relevant to citizenship in this context.